Performance evaluation of weak kaolin soils with waste-derived plastic granular inclusions - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Fahad, Alshawmar (Nature Publishing Group, 2025)
Sustainable geotechnical solutions are increasingly adopting recycled materials for ground improvement. However, the use of vertically embedded Acrylonitrile Butadiene Styrene (ABS) plastic waste columns, particularly with geotextile confinement, remains underexplored in existing literature, limiting their practical application. This study addresses that gap by evaluating the mechanical performance of kaolin clay reinforced with ABS columns of varying diameters and depths, both with and without geotextile encasement. The research aims to quantify strength improvements, identify optimal reinforcement configurations using geometric ratios, and develop a predictive regression model for practical use. Laboratory tests, including unconfined compression and unconsolidated undrained triaxial shear, showed that encapsulated ABS columns with 8 mm diameter and 50 mm depth enhanced unconfined compressive strength by up to 125.5% and increased effective cohesion from 22.0 to 70.9 kPa. Strength gains were primarily attributed to improved confinement and frictional resistance. A regression-based model was developed to estimate strength based on column geometry and placement parameters, aiding real-world applications. Additionally, incorporating recycled ABS plastic reduces landfill waste and offers a lower carbon footprint compared to conventional materials, reinforcing its potential as an effective and sustainable solution for soil stabilization.